Depositional Environment of the Batuasih Formation on the Basis of Foraminifera Content: A Case Study in Sukabumi Region, West Java Province, Indonesia - Hendrizan, M.; Praptisih, Praptisih; Putra, Purna S. (Indonesian Journal on Geoscience, 2012)
DOI:Â 10.17014/ijog.v7i2.139The research was carried out on the sediments of the Batuasih Formation cropping out at Batuasih Village, Cibatu River, Padaarang Sukabumi. Data obtained from field observation, as well as foraminifera and sedimentology analyses conducted in the laboratory, were used to interpret its depositional environment. The investigation was focused on planktonic and benthic foraminiferal assemblages for depositional environment interpretation that might not be used by previous researchers. The Batuasih Formation is composed of black shaly claystone, where the lower part is rich in clay ball, and limestone intercalations in the upper part of the formation. In Cibatu Section, no clay balls is recognized in the lower part, but intercalations of limestone still occur. However, a contrast difference is found in Padaarang section, where green claystone interbeds with fine-grained sandstone. The Batuasih Formation conformably overlies the Walat Formation containing conglomerate. Foraminifera fossil found in the Batuasih Formation consists of bad preserved black benthic and planktonic foraminifera, more abundant towards the lower part of formation. Based on foraminifera assemblage comprising genus Uvigerina, Cibicides, Elphidium, Operculina, Bulimina, Bolivina, Eponides, and Neoconorbina, supported by sedimentology data, the Batuasih Formation was deposited in a shallow to deep marine environtment, during Early Oligocene (P19) time. Upwards to be the Rajamandala Formation, the depositional environment tends to be shallower gradually.